Osteoarthritis: a narrative review of molecular approaches to disease management - Loay A. Salman (14150322) (2023)
Osteoarthritis (OA) is a chronic, progressive degenerative whole joint disease that affects the articular cartilage, subchondral bone, ligaments, capsule, and synovium. While it is still believed to be a mechanically driven disease, the role of underlying co-existing inflammatory processes and mediators in the onset of OA and its progression is now more appreciated. Post-traumatic osteoarthritis (PTOA) is a subtype of OA that occurs secondary to traumatic joint insults and is widely used in pre-clinical models to help understand OA in general. There is an urgent need to develop new treatments as the global burden is considerable and expanding. In this review, we focus on the recent pharmacological advances in the treatment of OA and summarize the most significant promising agents based on their molecular effects. Those are classified here into broad categories: anti-inflammatory, modulation of the activity of matrix metalloproteases, anabolic, and unconventional pleiotropic agents. We provide a comprehensive analysis of the pharmacological advances in each of these areas and highlight future insights and directions in the OA field. Other Information Published in: Arthritis Research & Therapy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s13075-023-03006-w